BIOLOGICAL ACTIVITIES OF NOVEL IN VITRO RAISED STEVIA PLANT - Sharma, Neeta Raj; Meshram, Vineet; Gupta, Mahiti (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This communication explores a lead fraction from methanolic extract of novel Stevia species raised under in vitro conditions for its various biological activities. Methods: The dried Stevia leaves were crushed in methanol to get the polar extract. This methanol extract was tested for pancreatic lipase and alpha-amylase inhibitory activity using quantitative plate assays. Antibacterial property of the extract was also evaluated against Staphylococcus epidermidis, Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa. Further, the antioxidant potential was evaluated using 1,1-diphenyl-2-picrylhydrazyl. Results: The methanolic extract inhibited pancreatic lipase with IC50 of 5.74 Î¼g/ml in a similar manner to a well-known anti-obesity drug in the market orlistat. The methanolic extract also showed a better pancreatic Î±-amylase inhibitory activity (IC50=88 Î¼g/ml) than acarbose. Further, the lead fraction exhibited 88.48% antioxidant activity. It also exhibited broad spectrum antimicrobial activity against the spectrum of Gram-positive and Gram-negative bacteria tested under laboratory conditions with a minimal inhibitory concentration ranging from 1.95 to 31.25 Î¼g/ml. Conclusion: Thus, this study signifies the vast potential of the lead fraction from a novel Stevia species for further development into a herbal formulation for prevention of various infectious and non-infectious diseases.